Nathan B. answered • 10/03/18

Tutor

5
(20)
Elementary and Algebraic skilled

So here's what we know:

a = b - 1 (the first integer is 1 less than the middle)

c = b + 1 (the last integer is 1 more than the middle)

a + c = 5b - 57 (the first and last's sum is equal to 57 less than 5 times the middle)

We have values for some of our variables, so plug them in:

b - 1 + b + 1 = 5b - 57

Simplify:

2b = 5b - 57

Are you able to isolate b from here? Subtract 5b from both sides, then divide both sides by the remaining coefficient to get your answer for the middle integer.